MEMBANGUN PRESTASI SEKOLAH MELALUI BENCHMARKING TEKNOLOGI TEPAT GUNA: STUDY KASUS SMK PGRI SUBANG - Abdullah Abdullah; Nurudin Nurudin; Syaefuddin Syaefuddin (Edulead : Journal of Education Management, 2021)
This best practice is motivated by complex issues, among others, SMK PGRI Subang is the only SMK PGRI Subang in Subang Regency that has an ISO certificate. In addition, the education unit level curriculum document as a reference in the implementation of learning and education is fully structured. This can be seen from the learning evaluation documents and assessments that are completely administered. Likewise with the conditions and characteristics of students, most of whom have UN scores according to school quality standards. To form a school that excels, the school is improving in every way. One of the efforts made is to apply the "Appropriate Technology" strategy (Problem Response, Motivation, Communication and Spirituality) which aims to improve school achievement. This research was carried out in four steps, namely problem response, motivation, communication and spirituality. The impact of the Appropriate Technology strategy is (1) students are enthusiastic in learning, (2) are able to move teachers to implement innovative learning, (3) for schools are public interest, are trusted by stakeholders, refer to other schools and receive assistance from stakeholders. Abstrak Best Practice ini dilatarbelakangi oleh persoalan yang kompleks, antara lain SMK PGRI Subang merupakan satu-satunya SMK PGRI Subang di Kabupaten Subang yang memiliki sertifikat ISO. Selain itu, dokumen kurikulum tingkat satuan pendidikan sebagai acuan dalam penyelenggaraan pembelajaran dan pendidikan tersusun secara lengkap. Hal itu terlihat dari dokumen evaluasi belajar dan penilaian yang diadministrasikan dengan lengkap. Begitu pula dengan kondisi dan karakteristik siswa yang sebagian besar memiliki nilai UN sesuai standar mutu sekolah. Untuk membentuk sekolah yang berprestasi, sekolah berbenah dalam segala hal. Salah satu upaya yang dilakukan adalah menerapkan strategi “Teknologi Tepat Guna” (Tanggap Masalah, Motivasi, Komunikasi dan Spiritual) yang bertujuan untuk meningkatkan prestasi sekolah. Penelitian ini dilaksanakan dalam empat langkah, yaitu tanggap masalah, motivasi, komunikasi dan spiritualitas. Adapun dampak dari strategi Teknologi Tepat Guna adalah (1) siswa antusias dalam belajar, (2) mampu menggerakkan guru untuk menerapkan pembelajaran inovatif, (3) bagi sekolah adalah diminati masyarakat, dipercaya stakeholder, rujukan sekolah lain dan mendapat bantuan dari pemangku kepentingan.